Kumon’s Learning Model with the Assistance of Multiplication Table in Observed from Achievement and Discipline Attitude In Mathematics Learning - Indriastuti, Agni Nur Indriastuti; Rusnilawati (Universitas Pendidikan Ganesha, 2022)
Mathematics is a subject that should be given to all students to equip them with logical, analytical, systematic, critical and creative thinking skills, and collaboration skills. However, determining effective learning models and media to improve student achievement and discipline is very difficult. One of the solutions for determining interactive media is a multiplication table with the Kumon model. The purpose of this study was to analyze the multiplication table-assisted Kumon learning model on achievement and discipline in mathematics learning. The research method in this research is an experimental design by comparing the experimental and control classes. This study used data collection techniques which included experimenting, observing, and documenting. The analysis used in this study consisted of standardized tests (normality), homogeneity checks, and hypothesis testing. The results of the study showed that there was an increase in the achievement and discipline of third-grade elementary school students before and after using the Kumon learning model with media multiplication tables so that it could be assessed that the learning model was effective, in terms of student achievement and discipline.